Data extraction and preparation to perform a sentiment analysis using open source tools: The example of a Facebook fashion brand page - Teixeira, António; Laureano, Raul M. S. (12th Iberian Conference on Information Systems and Technologies (CISTI'2017), 2017)
Social Media is a subject that is being very discussed in the present. The increasing availability of internet and the growth of Social Media platforms drove organizations attention to Opinion Mining and Sentiment Analysis. One of the most popular Social Media Platform is Facebook. In this Social Media Platform users/consumers can express their feelings with comments or with emotion buttons. With the functionalities of Facebook, they can criticize, praise, suggest or expect. The user's interactions with a brand page as posts, likes, shares or comments are getting more relevance in present days. The analysed data can give to decision-makers new approaches to run their business, understand their brand value against the competitors or even understand better what are the evaluations of customers or potential customers about the brand products or services. The purpose of this paper is to explain how to extract and prepare data collected in Facebook using open-source tools to perform a Sentiment Analysis.